Precision medication: An illustrative case series guiding the clinical application of multi‐drug interactions and pharmacogenomics. Issue 2 (23rd December 2019) - Bain, Kevin T.; McGain, David; Cicali, Emily J.; Knowlton, Calvin H.; Michaud, Veronique; Turgeon, Jacques
Abstract: Precision medication entails selecting the precise medication, dose, and timing of administration. Multi‐drug interactions and genetics significantly affect precision medication. In this article, we present two simulated cases for real‐world applications of precision medication. Clinicians may need to acquire additional skills to apply the principles illustrated by these cases. Abstract : Precision medication entails selecting the precise medication, dose, and timing of administration. Multi‐drug interactions and genetics significantly affect precision medication. In this article, we present two simulated cases for real‐world applications of precision medication. Clinicians may need to acquire additional skills to apply the principles illustrated by these cases.